2016
DOI: 10.1525/sod.2016.2.4.342
|View full text |Cite
|
Sign up to set email alerts
|

World Society and the Global Foreign Aid Network

Abstract: This article analyzes the relationship between foreign aid and globalization to explain developing country ties to world society and argues that foreign aid can be viewed as a recursive mechanism through which donor states refine and spread international norms and organizational ties. Using network data on foreign aid relationships between countries this article analyzes the effects of aid on human rights treaty ratification and international organization memberships in a sample of 135 less developed countries… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 50 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…When considering aid's role in World Society more generally, our results support the idea that sector-focused foreign aid can influence the diffusion/adoption of common models by states. This is in keeping with our hypotheses, and with earlier research on aid from a World Society perspective which theorizes a diffusion role for aid (Swiss, 2016b(Swiss, , 2016c. Still, our evidence suggests that aid's influence on isomorphism may have its limits when it comes to supporting not only the spread of models, but their institutionalization and efficacy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…When considering aid's role in World Society more generally, our results support the idea that sector-focused foreign aid can influence the diffusion/adoption of common models by states. This is in keeping with our hypotheses, and with earlier research on aid from a World Society perspective which theorizes a diffusion role for aid (Swiss, 2016b(Swiss, , 2016c. Still, our evidence suggests that aid's influence on isomorphism may have its limits when it comes to supporting not only the spread of models, but their institutionalization and efficacy.…”
Section: Discussionsupporting
confidence: 90%
“…Foreign aid's role in funding the diffusion and institutionalization of world society norms has only recently become a focus of research (Fejerskov, 2015;Peterson, 2014;Swiss, 2016bSwiss, , 2016cSwiss, , 2017Velasco, 2020). This research has shown that the more ties to bilateral aid donors that states have, the more likely a country is to adhere to world society human rights norms and join international organizations (Swiss, 2016b). For instance, Velasco (2020) shows that countries receiving aid from more donor countries, and those receiving more aid overall are predicted to offer more protections to LGBT rights.…”
Section: Aid and The World Societymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we are aware of no prior published work in economics that embed network measures in standard aid–growth models. In sociology, Swiss (2016) employs network analysis to explore the effects of aid on human rights treaty ratification and international organization memberships. Swiss (2017) further explores the effect of global ties on the foreign aid allocation, which provides an alternative explanation (institutionalist motives) for foreign aid.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the structure of global development cooperation, including aid, has received only scant attention in this context. There are indeed a few notable studies that employ network analysis to study aid [15][16][17][18][19]. Many of these studies calculate node-level local measures (e.g., degree centrality and eigenvector centrality) from given network representations, and then input these quantities into regression equations that largely model state-level behavior and/or state-to-state dyadic relationships.…”
Section: Introductionmentioning
confidence: 99%